Seascapes are landscapes after all; Comment on Manderson (2016): Seascapes are not landscapes: an analysis performed using Bernhard Riemann's rules. ICES Journal of Marine Science, 73:1831–1838. (20th June 2017) - Bell, Susan S.; Furman, Bradley T.
Abstract: Recently, Manderson (2016, Seascapes are not landscapes: an analysis performed using Bernhard Riemann's rules: ICES Journal of Marine Science, 73: 1831-1838) argued that landscape ecology approaches developed in terrestrial habitats have little practical application for the study of marine "seascapes". Here, we offer a contrasting perspective to this over-generalization. We first focus on historical uses of the term "seascape" to delineate the wide range of habitats that have been designated as such. After providing a brief overview of the study of seascape ecology, we argue that concepts and methodology originating from terrestrial disciplines have, in fact, provided an important cornerstone for investigating the dynamics of nearshore marine ecosystems. We present examples of coastal seascape research that have successfully applied terrestrial landscape theory and revisit points raised by Manderson regarding the application of landscape approaches to the marine environment. Overall, we contend that Manderson's thesis may apply to some, but not most, use of landscape constructs for investigating aquatic environments. Moreover, we suggest that the study of coastal landscapes will continue to yield valuable insight into the spatiotemporal workings of aquatic ecosystems, and that this particular avenue of ecological investigation will only increase in its relevance as human impacts intensify.